Religion und Stadtentwicklung im Islam - das Beispiel Teheran/ Iran - Ehlers, Eckart; Momeni, Mostafa (ERDKUNDE, 2002)
It is the basic argument of this paper that there is a close interrelationship between urban development and religious endowments. Teheran, capital of the Islamic Republic of Iran, serves as a case study for this interrelationship. Based on archival research it becomes apparent that in the early phases of the development of the capital under Qajar and Pahlavi rule both religious endowments (waqf, habous) and secular endowments (bonyad) have played major roles for urban development. Both types of endowments are likewise important in the Islamic Republic of Iran, as exemplified by large scale urban housing projects and the constructions of religious monumental architecture. In all cases, endowment architecture results in ecologically questionable congestions of urban fabric and new social stratifications and structures of the Iranian capital.